Specific binding of estrogen receptor to the estrogen response element. - Klein-Hitpass, L (1989)
Gene transfer studies have shown that estrogen regulation of specific genes is mediated by estrogen response elements (ERE). We report that binding of the estrogen receptor to the ERE can be detected by a gel retardation (band shift) assay. This binding interaction was highly sequence and receptor specific. Methylation interference analysis showed that the ERE contact sites of estrogen receptor displayed a perfect twofold rotational symmetry. This is compatible with estrogen receptor binding to the ERE as a head-to-head dimer.